The role of the pesantren law in strengthening the values of the boarding school tradition - Maulana, Ahmad Wahib; Sunarko, Moh. Heru (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
The Pesantren Law holds significant importance in strengthening and preserving the traditions of pesantren, enabling these institutions to continue shaping the character and morals of the younger generation in alignment with noble Islamic values. This study examines the role of the Pesantren Law in reinforcing pesantren traditions at Pondok Pesantren Al-Arifiyah, Pekalongan City. Employing a qualitative case study approach, the findings reveal two key roles of the Pesantren Law. First, the administrative aspect enhances the values of simplicity, humility (ketawadhu'an), knowledge, and sincerity embedded in the kitab kuning (classical Islamic texts) curriculum, which must be integrated into the Simba PD Pontren system managed by the Indonesian Ministry of Religious Affairs. Second, the financial role is evident in the utilisation of the Smart Indonesia Programme, providing learning capital for santri (students) at Al-Arifiyah. The educational outcomes of the santri are showcased during the traditional Haflah Akhirussanah ceremony, reflecting values of gratitude and creativity. This study underscores the critical role of the Pesantren Law in institutional development and the preservation of pesantren traditions while supporting student growth and educational achievements.